Socio-demographic Profile and Outcome of Vasectomy at a Tertiary Hospital of Karnali Province - Devkota, Harihar; Menyangbo, Suryaman; Neupane, Manik; Samal, Anup Mangal; Sanjel, Sesananda (Journal of Karnali Academy of Health Sciences, 2020)
Background: The one and only permanent sterilization technique for men is vasectomy. It is a simple, safe and very effective procedure. However, it is perceived wrongly especially in the rural settings, ruled by social stigma and false belief. It is perceived as to falsely decrease the performance which often affects the satisfaction and the completeness of the procedure. This study aims to determine the sociodemographic profile of the vasectomy, the completeness of the procedure and its related outcomes at Tertiary hospital of Karnali Province. Methods: It is a hospital-based cross sectional study among the patients who underwent vasectomy at Karnali Academy of Health Sciences during the period of July 2019 to June 2020 AD. The data were retrieved from the register. The patients were then interviewed via telephone and the variables were recorded and analyzed using SPSS version 16. Results: Out of the total 67 cases, majority were Chhetri (59.7%) from Jumla and farmer (58.2%) by occupation. About 45% were educated till secondary level while 9% were illiterate. The mean age of male undergone vasectomy was 30 years. Ibuprofen prescribed after the procedure was adequate for analgesia in 85.1% of the people and 98.5% of people were satisfied with the procedure. There were no complications in two third (67.16%), however 13.43% had chronic scrotal pain, 11.94% had acute scrotal hematoma, 4.48% had epididymitis and 2.99% had infection of the scrotum. There was no issue with sexual frequency in 83.58% and 59.7% of the clients had not completed semen analysis. Conclusion: The post procedural issues after vasectomy were affirmative which showed low complications and procedural satisfactions. However the compliance with completion of semen analysis was not promising. The study can guide path for the further studies